2018
DOI: 10.1159/000496447
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis on the Relationship Between Hair Dye and the Incidence of Non-Hodgkin’s Lymphoma

Abstract: Background: Epidemiologic studies have suggested hair dye to be a risk factor for many cancers. However, previous studies on the association between the personal use of hair dye and risk of non-Hodgkin’s lymphoma (NHL) have been inconclusive. Methods: The PubMed, Embase, Cochrane Library, and Web of Science databases, as well as the references cited in included studies, were searched for relevant studies up to February 10, 2015. Odds ratios (OR) with 95% confidence intervals (CI) were applied to assess the str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Park et al, 2019 reported that volatile organic compounds (VOCs) and phthalates concentrations of sanitary pads and diapers were significantly higher than those found in common commercial was used in more than 80% of permanent dyes, is frequently reported to cause vascular neuroedema, acute renal failure or bladder cancer [47] . Qin et al, 2019 reported that hair dye use increases the risk of non-Hodgkin's lymphoma, especially for females [48] . OTC use of cosmetic lenses is rapidly increasing.…”
Section: Introductionmentioning
confidence: 99%
“…Park et al, 2019 reported that volatile organic compounds (VOCs) and phthalates concentrations of sanitary pads and diapers were significantly higher than those found in common commercial was used in more than 80% of permanent dyes, is frequently reported to cause vascular neuroedema, acute renal failure or bladder cancer [47] . Qin et al, 2019 reported that hair dye use increases the risk of non-Hodgkin's lymphoma, especially for females [48] . OTC use of cosmetic lenses is rapidly increasing.…”
Section: Introductionmentioning
confidence: 99%
“…p-Phenylenediamine (PPD), which was used in more than 80% of permanent dyes, is frequently reported to cause vascular neuroedema, acute renal failure or bladder cancer [47]. Qin et.al, 2019 reported that hair dye use increases the risk of non-Hodgkin's lymphoma, especially for females [48]. OTC use of cosmetic lenses is rapidly increasing.…”
Section: Introductionmentioning
confidence: 99%